V. 2 - Ratanlal (Gurgaon, 2016)
This classic Ratanlal and Dhirajlal's The Indian Penal Code, first published in 1896 is a section wise commentary on the Indian Penal Code. This edition has been extensively and meticulously revised taking into account the changes brought about by recent legislative amendments as well as judgments of higher courts. Radically revised, the edition exhaustively covers the consequences of the Criminal Law (Amendment) Act, 2013.
Keywords: Criminal law